2021
DOI: 10.2340/jrm.v53.807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-grip myoelectric prosthetic hands on daily activities, pain-related disability and prosthesis use compared with single-grip myoelectric prostheses: A single-case study

Abstract: Objective: To evaluate the effect of multi-grip myoelectric prosthetic hands on performance of daily activities, pain-related disability and prosthesis use, in comparison with single-grip myoelectric prosthetic hands. Design: Single-case AB design. Patients: Nine adults with upper-limb loss participated in the study. All had previous experience of single-grip myoelectric prostheses and were prescribed a prosthesis with multi-grip functions. Methods: To assess the changes in daily activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Further development are needed with inertial sensors in order to record longer activities in more ecological situations. Similarly, this method could be useful to evaluate other innovative medical devices such advanced polydigital hand [82], more flexible wrist prostheses, or the impact of PLOS ONE artificial proprioceptive feedback. Kinematic analysis could be operational for the choice and prescription of prosthesis and in order to guide rehabilitation techniques while preventing musculoskeletal disorders.…”
Section: Perspectivesmentioning
confidence: 99%
“…Further development are needed with inertial sensors in order to record longer activities in more ecological situations. Similarly, this method could be useful to evaluate other innovative medical devices such advanced polydigital hand [82], more flexible wrist prostheses, or the impact of PLOS ONE artificial proprioceptive feedback. Kinematic analysis could be operational for the choice and prescription of prosthesis and in order to guide rehabilitation techniques while preventing musculoskeletal disorders.…”
Section: Perspectivesmentioning
confidence: 99%
“…The case report of van der Niet et al found no significant differences on OPUS-UEFS scores between an MHP and an SHP hand [ 8 ]. Additionally, five studies showed no differences between the two hands on the SHAP and BBT [ 8 10 , 17 , 18 ]. Only one study stated an increase in fine motor control with an MHP [ 6 ], although it should be noted that this research focussed on the Michelangelo hand, which was excluded from the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation measures that have been mentioned in the literature are the Dutch version of the Quebec User Evaluation of Satisfaction with assistive technology (D-QUEST), visual analogue scales (VAS-scores), and the electronic patient-reported outcome measure (ePROM) to assess the preferred usage features of upper limb prostheses (PUF-ULP) [ 19 ]. Two previous studies showed that users were more satisfied with the MHP than with the SHP [ 8 , 18 ]. However, another study revealed that half of the MHP users switched to a different terminal device within a year [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, power grip was used more often at home (median use of 52%) than during to in-lab testing (21%) while pinch and lateral grip were used less at home (4% and 14%, respectively) than during in-lab testing (11% and 25%, respectively). Widehammar et al [28] investigated the effect of multi-vs single-grip myoelectric prosthetic hands using the Ottobock Bebionic hand (14 grip types). Individuals with a transcarpal amputation controlled the hand using direct control including myoelectric switching (in combination with using a button on the hand) for the multi-grip option.…”
mentioning
confidence: 99%
“…Over six months of home use, performance and satisfaction with the multi-grip hand increased over time. While it was possible for individuals to control the multi-grip hand with standard 2-site direct control, they did not evaluate grip switching nor whether users selected the appropriate grip [28].…”
mentioning
confidence: 99%